2006
DOI: 10.1111/j.1600-6143.2006.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Superior Prevention of Acute Rejection by Tacrolimus vs. Cyclosporine in Heart Transplant Recipients—A Large European Trial

Abstract: We compared efficacy and safety of tacrolimus (Tac)-based vs. cyclosporine (CyA) microemulsion-based immunosuppression in combination with azathioprine (Aza) and corticosteroids in heart transplant recipients. During antibody induction, patients were randomized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 31 publications
5
82
1
9
Order By: Relevance
“…Tacrolimus not only offers better protection against acute rejection compared to cyclosporine [131][132][133] , but it is also superior against CAV [134] . Moreover, Petrakopoulou et al [135] showed that tacrolimus is better than cyclosporine in the prevention of microvascular endothelial dysfunction.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…Tacrolimus not only offers better protection against acute rejection compared to cyclosporine [131][132][133] , but it is also superior against CAV [134] . Moreover, Petrakopoulou et al [135] showed that tacrolimus is better than cyclosporine in the prevention of microvascular endothelial dysfunction.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…Introduction of CNIs shifted the paradigm of solid organ transplant. Although there is improved survival and reduced burden of rejection with CNI use, increased incidence of post-transplant hypertension is observed since the introduction of CNI therapy [112]. CNIs are known to cause hypertension in post-transplant patients by inducing endothelial dysfunction and imbalance between vasodilator and vasoconstrictive substances.…”
Section: Hypertensionmentioning
confidence: 99%
“…Multiple agents are frequently needed [14]. It is known that the frequency of HTN is higher with Cyclosporine (CSA) compared to Tacrolimus (TAC) [15]. However, TAC cannot be recommended solely on this basis as it could double the risk of new onset diabetes itself a risk factor for CKD.…”
Section: Treatment Of Htnmentioning
confidence: 99%
“…However, TAC cannot be recommended solely on this basis as it could double the risk of new onset diabetes itself a risk factor for CKD. Many agents have been studied in animal models but few have been assessed in patients [15].…”
Section: Treatment Of Htnmentioning
confidence: 99%